Reflecting internalization and manifestation of Sundanese cultural values on leadership communication styles in the mining industry (an ethnographic study at PT Petrosea, Tbk.) - Fazarullah , Dwirizky; Heikal, Jerry (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
This research explores the influence of Sundanese cultural values on leadership communication styles at PT Petrosea, a mining company in Indonesia. This qualitative research employs an ethnographic approach and involves three leaders at PT Petrosea who have a strong Sundanese cultural background. Data were collected through participant observation and in-depth interviews, and then analyzed qualitatively. The results show that Sundanese cultural values, such as "someah hade ka semah" (being friendly and kind to everyone), "silih asih, silih asah, silih asuh" (loving each other, educating each other, and caring for each other), and "hade tahta hade bahasa" (harmony between position and speech), are internalized and manifested in their leadership styles. These values are reflected in communication styles that are "rame" (vivacious, lively, together) and "hegar" (warm, cheerful, positive), emphasizing harmony and teamwork, as well as the ability to adapt to various situations. This research recommends integrating local cultural values into the development of contextual and sustainable leadership models.